E-Learning During Pandemic - Perspective of Interns from A Private DentalInstitution in Bangalore - A Cross-Sectional Study - Sujithra S; Misbah Noorain; Suchetha A; Deepti Vadavi; Harikiran A G; Vinodhini K (RGUHS Journal of Dental Sciences)
Background The Coronavirus disease 2019 COVID-19 pandemic arguably represents the worst public health crisis of the 21st century. There is a paucity of literature examining the interns perspective in dentistry on e-learning during the pandemic.Methodology A cross-sectional study was conducted from December 2020 to June 2021 with the target population as interns of DAPM RV Dental College in Bangalore Karnataka who were in their final year during the onset of the pandemic. A convenient sampling method was incorporated. Primary data were collected using a questionnaire under six domains via Google forms and distributed to all interns pursuing internship at DAPMRV Dental College through a WhatsApp group.Results The outcome of our survey confirmed that during the COVID-19 pandemic and thereafter reforms in dental clinical training and assessment strategies should be more extensive using virtual reality haptic labs simulation technologies and reliable tools that support attaining adequate skills and objective evaluating studentrsquos clinical abilities in comparison with e-learning. It was also observed that gender did not significantly influence the responses of the study participants.Conclusion Our study showed that students partially appreciated the new system with e-lectures and discussion forums. However they expressed missing on-in-campus educational experiences.